Injecting Immunosuppressive M2 Macrophages Alleviates the Symptoms of Periodontitis in Mice - Miao, Yibin; He, Liuting; Qi, Xiaoyu; Lin, Xiaoping (Frontiers in Molecular Biosciences, 2020)
Periodontitis is the second most common oral disease affecting tooth-supporting structures. The tissue damage is mainly caused by the excessive secretion of proinflammatory cytokines by immune cells. Macrophages are a type of antigen-presenting cells that influence the adaptive immunity function. We used a unique set of cytokines, i.e., a combination of IL-4, IL-13, and IL-10, to stimulate macrophages into a subset of M2 polarization cells that express much higher levels of ARG-1, CD206, and PDL-2 genes. A mixed-lymphocyte culture was used to test the immune suppression potential, which showed that this subset of macrophages could increase IL-2 secretion and suppress IL-17, IL-6, and TNF-α secretion by splenocytes. The gram-negative bacterial species P. gingivalis was used to initiate an inflammatory process in murine periodontal tissues. In the meantime, cell injection therapy was used to dampen the excessive immune reaction and suppress osteoclast differentiation during periodontitis. The results indicated that mice in the cell injection group exhibited less osteoclast activity within the periodontal ligament region than in the periodontitis group. Moreover, the injection of M2 macrophages sustained the regulatory population ratio. Therefore, the M2 macrophages induced IL-4, IL-13, and IL-10 combination, with tremendous immune modulation ability in treating periodontitis.